COMMUNITY PERCEPTIONS OF DISASTER MANAGEMENT IN SUNGAI BAKUNG VILLAGE - Sugiannor, Sugiannor; Ridwan, Muhammad Nur Iman; Junaidy, Junaidy (International Conference On Social Science Education, 2023)
Disaster management is preparing for, responding to, and recovering from natural or manufactured disasters. Disaster management aims to reduce the impact of disasters; help affected communities return to normalcy as soon as possible, and ultimately save lives. In 2022, there will be 76 natural disasters in South Kalimantan Province, with natural disasters dominated by floods 45 times, landslides six times, and typhoons 25 times. This data was obtained from the Tagana Social Service of South Kalimantan. This study aims to analyse how the response to natural disasters that seem to be happening every year must be used as material for evaluation for the government on how to make contingency policies for this situation before, during and after disasters, especially floods, which have been made several areas of Banjar district prone to stagnant water. Affect the life of the community. The research method used is a qualitative methodology with a research approach that emphasises the subjective interpretation of social phenomena. This methodology relies on collecting data through interviews, observation and document analysis to explore the complexities of social interactions and experiences. The results of this study indicate that there has not been or has not been an optimal effort from the government in managing disasters, creating a public perception of a disaster situation as if there were no attention except when the disaster occurred.